QUANTUM CHEMISTRY AND CLASSICAL SIMULATIONS OF METAL COMPLEXES IN AQUEOUS SOLUTIONS - Sherman D.M. (My University, 2001)
It has long been known that the solubilities of sulfide ore minerals in hydrothermal fluids results from the complexation of metals such as Cu, Zn and Fe by Cl and HS ligands (Seward and Barnes 1997). Complexation of heavy metals such as As, Pb and Cd by mineral surfaces controls the mobility of such metals in the environment. Geochemists need to have a reliable thermodynamic data set to predict mineral solubilities and metal sorption reactions. Such data are found by fitting measured solubilities and sorption isotherms to a set of stability constants for aqueous and surface complexes. However, fits to experimental data are often non-unique and depend on the speciation model; an independent way to determine the nature of metal complexes in aqueous solutions and on mineral surfaces is needed. ### Experimental methods Direct experimental determination of metal speciation in aqueous solutions and on mineral surfaces can be done using spectroscopy. With an appropriate cell, in situ spectroscopic measurements can on aqueous solutions as a function of pressure and temperature. Raman spectroscopy is especially useful for aqueous solutions. Recent investigations include Au3+ (Pan and Wood 1991; Peck et al. 1991; Murphy and LaGrange 1998), Cu and Zn (Helz et al. 1992; Rudolph and Pye 1999) and Cd2+ (Rudolph and Pye 1998). For some complexes, however, Raman spectra require very high concentrations. Under such conditions, the complexes that form will usually differ from those in more dilute geochemical fluids. The situation is even worse with neutron scattering where metal concentrations on the order of 1 M are required (e.g., Enderby and Nielson 1981; Cossy et al. 1988). Optical absorption spectroscopy can be used to investigate very low concentrations if ligand to metal charge-transfer transitions are exploited. However, we need to know absorption coefficients and band assignments. Extended X-ray absorption …